Antimicrobial susceptibility patterns of Î²-lactamase producing Staphylococcus Aureus - Kawsar, Narjis Maliha; Mondal, Md Eunus Ali; Khan, Nizamul Karim; Jubaida, Nishat; Chowdhury, Jamal Pasha; Khan, Luthunnahar (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1838 JAFMC Bangladesh Vol.4(2) 2008 14-17